Hysterectomy—Current Methods and Alternatives for Benign Indications. (28th July 2010) - Papadopoulos, Michail S.; Tolikas, Athanasios C.; Miliaras, Dimosthenis E.
Abstract : Hysterectomy is the commonest gynecologic operation performed not only for malignant disease but also for many benign conditions such as fibroids, endometrial hyperplasia, adenomyosis, uterine prolapse, dysfunctional uterine bleeding, and cervical intraepithelial neoplasia. There are many approaches to hysterectomy for benign disease: abdominal hysterectomy, vaginal hysterectomy, laparoscopic assisted vaginal hysterectomy (LAVH) where a vaginal hysterectomy is assisted by laparoscopic procedures that do not include uterine artery ligation, total laparoscopic hysterectomy (TLH) where the laparoscopic procedures include uterine artery ligation, and subtotal laparoscopic hysterectomy (STLH) where there is no vaginal component and the uterine body is removed using a morcelator. In the last decades, many new techniques, alternative to hysterectomy with conservation of the uterus have been developed. They use modern technologies and their results are promising and in many cases comparable with hysterectomy. This paper is a review of all the existing hysterectomy techniques and the alternative methods for benign indications.